2021
DOI: 10.1021/acs.inorgchem.0c03763
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Effect of Palladacycles: Targeting A2780 Ovarian Carcinoma Cells and Modulation of Angiogenesis

Abstract: Palladacycles are versatile organometallic compounds that show potential for therapeutic use. Here are described the synthesis and characterization of mono-and dinuclear palladacycles bearing diphosphines. Their biological effect was investigated in A2780, an ovarian-derived cancer line, and in normal dermal fibroblasts. The compounds displayed selective cytotoxicity toward the A2780 cell line. Compound 3 decreased the cell viability through cell cycle retention in G0/G1, triggered apoptosis through the intrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…Some years ago, the chick chorioallantoic membrane (CAM) model was described as an excellent in vivo model to study the effect of newly identified molecules in angiogenesis and tumor invasion of colorectal, prostate, brain cancer, and ovarian cancers . Moreover, in vivo model toxicity effects might also be studied, as recently described by us for palladacycles . This prompted us to also test compounds 1 and 3 in this model in terms of toxicity and antiangiogenic potential using as a model ex ovo CAM …”
Section: Resultsmentioning
confidence: 99%
“…Some years ago, the chick chorioallantoic membrane (CAM) model was described as an excellent in vivo model to study the effect of newly identified molecules in angiogenesis and tumor invasion of colorectal, prostate, brain cancer, and ovarian cancers . Moreover, in vivo model toxicity effects might also be studied, as recently described by us for palladacycles . This prompted us to also test compounds 1 and 3 in this model in terms of toxicity and antiangiogenic potential using as a model ex ovo CAM …”
Section: Resultsmentioning
confidence: 99%
“…They can be synthesized using bidentate bridging ligands (e.g., bidentate phosphine ligands), together with additional ligands selected for their capability to trigger interactions with a biomolecular target [ 192 , 193 ]. Several of these derivatives showed higher anticancer activity than the mononuclear complexes when tested in vitro and in vivo against different human tumours associated with several types of mechanisms of action, including DNA damage, inhibition of cancer cell metabolism, mitochondrial dysfunctions, apoptosis, and autophagy, as well as angiogenesis modulation [ 185 , 194 , 195 ]. More recently, a novel binuclear palladacycle derivative referred to as AJ-5 has shown in various experimental models in vitro to be particularly active, with a good safety profile in vivo.…”
Section: Palladiummentioning
confidence: 99%
“…To evaluate if the observed apoptosis induction in the HCT116 cell line is triggered by the intrinsic pathway, due to destabilization of mitochondria, changes in the mitochondrial membrane potential were evaluated using JC-1 dye (Abnova). This is a green fluorescent dye as a monomer; however, it will aggregate in the presence of a normal mitochondrial potential, which will cause a red-shift in emission spectra [97]. Measuring the green and red fluorescence by flow cytometry it is possible to calculate normalized ratios that can show us if there is an increase or decrease in the mitochondrial membrane potential (Figure 15).…”
Section: Evaluation Of Alterations In the Mitochondrial Membrane Potential Of Hct116 Cells Exposed To Complexes 1-3mentioning
confidence: 99%
“…Cells were also incubated with DMSO 0.1% (vehicle control) and cisplatin 15 µM (positive control). Following the manufacturer's instructions, after this incubation period, cells were detached with trypsin, washed with PBS 1× and incubated 15 min at room temperature with Annexin V-Alexa fluor 488 assay solution and 10 µg mL −1 propidium iodide [97,104]. An Attune acoustic focusing cytometer (ThermoFisher Scientific, Waltham, MA, USA) was used to analyze cells and the resulting information was processed with the respective Attune Cytometric Software 2.1 (ThermoFisher Scientific, Waltham, MA, USA).…”
Section: Evaluation Of Apoptosis Induction In the Hct116 Cell Line By Flow Cytometrymentioning
confidence: 99%
See 1 more Smart Citation